2013
DOI: 10.1097/ico.0b013e318269059b
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin/Ultraviolet A Crosslinking of the Paracentral Cornea

Abstract: The intended depth of CXL using current light sources is achieved only within the central area of the cornea. To provide CXL to the peripheral cornea, the ultraviolet beam either should have an improved intensity profile or may have to be decentered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 11 publications
3
34
0
3
Order By: Relevance
“…A study examining the peripheral effect of CXL, using OCT evaluation of the stromal demarcation line, showed that the depth of the CXL effect 3 mm away from the center of the cornea decreases to 65% of the central depth. Therefore, it was concluded that the intended depth of CXL using current light sources is achieved only within the central area of the cornea, and in order to provide CXL to the peripheral cornea, the ultraviolet beam either should have an improved intensity profile or may have to be decentered [151]. Two prospective studies evaluated the effect of CXL on the peripheral cornea.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study examining the peripheral effect of CXL, using OCT evaluation of the stromal demarcation line, showed that the depth of the CXL effect 3 mm away from the center of the cornea decreases to 65% of the central depth. Therefore, it was concluded that the intended depth of CXL using current light sources is achieved only within the central area of the cornea, and in order to provide CXL to the peripheral cornea, the ultraviolet beam either should have an improved intensity profile or may have to be decentered [151]. Two prospective studies evaluated the effect of CXL on the peripheral cornea.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the use of limbal protection during CXL should be considered. This is especially true for treatment of PMD, since the irradiated area in CXL for PMD may be decentered and thus positioned closer to the limbus [151]. …”
Section: Safetymentioning
confidence: 99%
“…В недавних исследовани-ях Koller и соавт. выявили, что демаркационная линия в 3-мм парацентральной зоне роговицы располагается на 65% более поверхностно, чем в центре [15]. Такую тенденцию отмечают Yam и соавт., указавшие на более глубокое расположение демаркационной линии в центре после стандартного CXL по сравнению с перифериче-скими зонами роговицы [14].…”
Section: Discussionunclassified
“…Эту гипотезу приводили в работах Koller и соавт. при изучении влияния мощности излучения в 3-мм зоне от центра в четырех квадрантах [15].…”
Section: Discussionunclassified
“…However, the follow-up period was 12 months. 42 Koller et al 43 examined the peripheral effect of CXL by evaluation of the stromal demarcation line by OCT, and they concluded that the targeted depth of CXL using current light sources is achieved within the central area…”
Section: Collagen Cross-linkingmentioning
confidence: 99%